PERILAKU KEBUTUHAN INFORMASI TERHADAP PERILAKU PENCARIAN INFORMASI PEMUSTAKA DI UPT PERPUSTAKAAN UNIVERSITAS BENGKULU - Lailatus Sa'diyah; Dara Ocka Himalaya; Purwaka (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Humaniora Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This research discusses the influence of information needs on the information-seeking behavior of library users at the UPT Library of the University of Bengkulu. Information needs are crucial in the decision-making process, problem-solving, and knowledge development. The more actively individuals engage in information-seeking, the more significant their information needs become. This study aims to determine whether there is an influence of information needs on the information-seeking behavior of library users at the UPT Library of the University of Bengkulu. The research method used is quantitative, and the statistical analysis tool employed is SPSS 25.0. The population of this study consists of 41,944 individuals, with a sample size of 100 respondents determined using the Proportionate Stratified Random Sampling technique. Data were collected through questionnaires and documentation. The data were analyzed using the Pearson Product-Moment Correlation test. The results of the product-moment correlation test showed a value of 0.702 between the information needs variable and the information-seeking behavior of library users at the UPT Library of the University of Bengkulu, indicating a strong correlation. The results of the study show that there is a significant influence of information needs on the information-seeking behavior of library users, with a strong correlation (0.60-0.799). The data were also analyzed using the Coefficient of Determination (R²) test. Based on the coefficient of determination calculation, it was found that the influence of information needs is 49.1%, while the remaining 50.9% of the information-seeking behavior is influenced by other variables.